Principles of entrepreneurship (ENT 530): Business model canvas: The Dee Dee’s Chocolate / Shawn O’Neill Anak Kelly - Kelly, Shawn O’Neill (2020)
The Dee Dee’s Chocolate are established in the end of the 2019 year. It is a business that are selling popular foods that are usually in high demand during public holidays which is in Raya and Gawai Festive season. Besides this business is a partnership business as the owner of this company which is Shawn O’niel anak Kellly as an owner and with it’s her partnership with his mother which is Nora anak Nanta. It is established due to his mother want to have a business which is selling food. This is because due to her business experience at her young age, it gets the attention of his son. Therefore, its owner is willingly help his mother to fulfil her ambition due to his son has the same passion as her. Besides that, we start selling our product at the end of 2019 till this day. Even though there are some calamities that makes a difficulty to sell our product, it is not enough to break our determination to do our best to make our business to become successful than before. As we can see from the festive season that will be coming soon on June, it is a perfect opportunity to sell our product due to its high demand from people especially at the Kota Samarahan area. Even though there are some slides up and down within our business, we are able to execute our business task with a little difficulty. This is because we are selling our product at reasonable price but at high quality that can satisfy the needs of our customer. Despite having a competitor that sells similar product as us within the Samarahan area, it gives us a healthy competition between each other as it has its own pro and cons while executing the business. In order to keep up with other competitor advantages, we offer a delivery service of our product towards our customer in order to keep our business in good condition. Due to its good feedback from our customer, it shows a positive sign to our business to operate in a long period of time. Without the feedback and critics from our customer, our businesses might not be as successful as it happens on this day. Thus, it gives us a chance to fulfil our goals to be a successful company that are selling the Kuih Chocolate Almond London and Chocolate Cookies without having a problem.